Osteology of Huabeisaurus allocotus (Sauropoda: Titanosauriformes) from the Upper Cretaceous of China. - Michael D D'Emic (Public Library of Science (PLoS), 2013)
Background The Late Cretaceous titanosauriform sauropod Huabeisaurus allocotus Pang and Cheng is known from teeth and much of the postcranial skeleton. Its completeness makes it an important taxon for integrating and interpreting anatomical observations from more fragmentary Cretaceous East Asian sauropods and for understanding titanosauriform evolution in general. Methodology/principal findings We present a detailed redescription of Huabeisaurus allocotus and a suite of anatomical comparisons with other titanosauriforms that demonstrate its validity via autapomorphies (e.g., division of some presacral vertebral laminae, reduced development of caudal ribs, the development of fossae relative to one another in caudal vertebral neural arches, high tibia-to-femur ratio). Huabeisaurus shares many features with other Cretaceous East Asian sauropods (e.g., pendant cervical ribs, anterior-middle caudal vertebrae with a nearly flat anterior centrum face and a concave posterior centrum face) that are absent in sauropods from other landmasses and strata, suggesting a close relationship among many of these forms within the clade Somphospondyli. Conclusions/significance Restudy of Huabeisaurus provides further evidence for the existence of a clade of somphospondylans--Euhelopodidae--mainly found in the Cretaceous of East Asia. Euhelopodidae represents a fourth example of the evolution of narrow crowns within Sauropoda, along with diplodocoids, brachiosaurids, and advanced titanosaurs (lithostrotians). Despite being known from fewer species than Diplodocoidea, Brachiosauridae, or Lithostrotia, euhelopodids possessed a broader range of tooth shapes than any of these clades, suggesting that euhelopodids exemplified a comparably broad range of feeding strategies and perhaps diets.